Legal perspectives to wards forgery, fraud and falsification of documents: recent development / Khairul Anuar Abdul Hadi and Halil Paino - Abdul Hadi, Khairul Anuar; Paino, Halil (Universiti Teknologi MARA Cawangan Selangor, 2016)
Forgery, fraud and falsification of documents are categorized as white color crime offences because they are associated with the modification of documents with the intention to deceive others and normally involve illegal monetary benefits. The existence of falsification and forgery is always associated with the intention to commit fraud. Both falsification and forgery have similarities in nature but carry a difference in provision under the statute. As far as this matter is concerned, to establish a successful prosecution and civil claim, the prosecutor and claimant must prove the intention and conduct of the accused person that falls under the respective statutory provision. However, in 2015, the application of evidential standard for these three types of crimes is the difference in civil action, even though this act is an offence under the Penal Code. In relation to that, this paper examines the relationship between fraud, forgery and falsification, evidential aspects together with the recent legal development and proposes a recommendation in relation to prosecutorial matters and civil claim.